Implementation evaluation of a local food based supplementary feeding program to support child nutrition in West Sulawesi, Indonesia - Irma Muslimin; Hasmar Fajriana; Andi Salim; Syafruddin Ali Salaka; Erna Amin (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2026)
Stunting remains a major public health problem in Indonesia, particularly in West Sulawesi, where structural and operational constraints limit the effectiveness of nutrition interventions. Local food-based supplementary feeding programs require systematic evaluation to understand their implementation performance within primary health care systems. This study aimed to evaluate the implementation of a local food-based supplementary feeding program to improve child nutritional outcomes in West Sulawesi. This descriptive qualitative study with a cross-sectional evaluation approach was conducted in the Mamuju, Majene, and Mamasa districts between November and December 2023. A total of 99 participants were involved, including 38 program managers and 61 mothers of beneficiary children. Data were collected through focus group discussions, in-depth interviews, structured questionnaires, and direct observations. Qualitative data were analyzed using thematic analysis, while quantitative data were summarized using descriptive statistics. Data triangulation was applied to enhance credibility. The results showed that the program was implemented in accordance with national technical guidelines but lacked locally adapted operational regulations. Most mothers (93.4%) reported weight gain among their children following program participation, and 23 of 54 undernourished children in one district showed short-term improvement in nutritional status. Key implementation challenges included limited nutrition personnel, delayed fund disbursement, inconsistent monitoring, and geographic barriers. In conclusion, the local food-based supplementary feeding program contributed to short-term improvements in child nutritional outcomes but faced operational constraints that limited optimal implementation. Strengthening governance, monitoring systems, and health workforce capacity is essential to improve program effectiveness.